2016
DOI: 10.4103/0971-4065.171232
|View full text |Cite
|
Sign up to set email alerts
|

A prospective audit of complications in 100 consecutive pediatric percutaneous renal biopsies done under real-time ultrasound guidance

Abstract: Despite being a common procedure, percutaneous renal biopsy (PRB) carries the potential for complications. The British Association of Paediatric Nephrologist (BAPN) has published standards for pediatric PRB. As Indian data are scarce, we conducted a prospective audit of 100 consecutive pediatric renal biopsies (60% males) under real-time ultrasound guidance. Nephrotic syndrome was the most common indication for PRB (68%) with minimal change disease (30%) and focal segmental glomerulosclerosis (25%) being the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Factors as uremia, arterial hypertension, and autoimmune disease may have contributed to this complication development. In the present study, major complications prevalence is much lower compared to other reports 12 to 30.8% of the cases [ 18 , 32 , 33 ]. This allows us to conclude that, in our center, percutaneous renal biopsy is a safe procedure with a major complications prevalence of less than 5%, concordant to previously established standards [ 32 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Factors as uremia, arterial hypertension, and autoimmune disease may have contributed to this complication development. In the present study, major complications prevalence is much lower compared to other reports 12 to 30.8% of the cases [ 18 , 32 , 33 ]. This allows us to conclude that, in our center, percutaneous renal biopsy is a safe procedure with a major complications prevalence of less than 5%, concordant to previously established standards [ 32 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Hussain F et al achieved the standard for the number of needle passes in 86.4% cases 10 . Whereas the Norwegian study and Sinha R. et al reported adequate biopsy material by ≤2 attempt in 85% and 72 cases respectively 6,7 . BAPN standard for adequacy is >95%.…”
Section: Resultsmentioning
confidence: 88%
“…Incidence was less reported by Varnell C D et al and Tondel C.et al and proportion was 3.5%. and 1.7% respectively 7,14,6 . Reported need for blood transfusion after renal biopsy was 0.9%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations